Design of special planar linkages - Zhao, Jingshan (Springer Tracts in Mechanical Engineering, 2014)
Planar linkages play a very important role in mechanical engineering. As the simplest closed chain mechanisms, planar four-bar linkages are widely used in mechanical engineering, civil engineering and aerospace engineering.   Design of Special Planar Linkages proposes a uniform design theory for planar four-bar linkages. The merit of the method proposed in this book is that it allows engineers to directly obtain accurate results when there are such solutions for the specified n precise positions; otherwise, the best approximate solutions will be found. This book discusses the kinematics and reachable workspace and singularity of a planar 3-RRR linkage, which can be used to analyze other planar linkages. Then a foldable stair that retains the walking conversions of human beings and all the merits of a concrete stair in civil engineering is described along with a lifting guidance mechanism that has the advantages of high strength, high rigidity, lightweight overconstraint trusses and motion flexibility. The method proposed in this book can be applied to other planar linkages.   This book offers a valuable resource for scientists, researchers, engineers, graduate students in mechanical engineering especially those interested in engineering design, robotics and automation.   Jingshan Zhao, Associate professor; Zhijing Feng and Fulei Chu, professor; Ning Ma, Dr., all work at the Department of Mechanical Engineering, Tsinghua University.